(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The banking sector is the main contributor of funds in the Malaysian economy, and it has gone through massive changes from liberalization, privatization, globalization, the entry of foreign banks, technological developments, and others. This development somehow has put pressure on employees, as they have to learn and adapt to the changes, and this will lead to a stressful work environment. Work stress is a serious worldwide public health concern, which will result in employees being less motivated and unproductive, affecting the employees’ physical and mental condition negatively. This study is conducted to find out the influence of job demands and job resources on work stress. 83 employees of Bank X were involved in this cross-sectional study. All the data were analyzed using a Statistical Package for the Social Sciences (SPSS). The findings show that job demand and job resources have a positive relationship with work stress. It is recommended for future study to conduct a longitudinal study and compare the findings with several other banks in order to get generality of the findings.